2022
DOI: 10.1302/2046-3758.112.bjr-2020-0482.r2
|View full text |Cite
|
Sign up to set email alerts
|

CircSCAPER contributes to IL-1β-induced osteoarthritis in vitro via miR-140-3p/EZH2 axis

Abstract: Aims Circular RNA (circRNA) S-phase cyclin A-associated protein in the endoplasmic reticulum (ER) (circSCAPER, ID: hsa_circ_0104595) has been found to be highly expressed in osteoarthritis (OA) patients and has been associated with the severity of OA. Hence, the role and mechanisms underlying circSCAPER in OA were investigated in this study. Methods In vitro cultured human normal chondrocyte C28/I2 was exposed to interleukin (IL)-1β to mimic the microenvironment of OA. The expression of circSCAPER, microRNA (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…This upregulation aggravates IL-1β-induced injury by downregulating IL-1β and reducing miR-142-5p in IL-1β-stimulated chondrocytes [ 138 ]. CircSCAPER promotes IL-1β-induced ECM degradation, proliferation arrest, and apoptosis enhancement in human chondrocytes by regulating the miR-140-3p/EZH2 axis [ 139 ]. The circRNA derived from vacuolar ATPase assembly factor ( VMA21 ) suppresses LPS-induced chondrocyte apoptosis in OA by decreasing the production of mature miR-103 [ 140 ].…”
Section: Ncrnas Involved In Cartilage Homeostasis and Oamentioning
confidence: 99%
“…This upregulation aggravates IL-1β-induced injury by downregulating IL-1β and reducing miR-142-5p in IL-1β-stimulated chondrocytes [ 138 ]. CircSCAPER promotes IL-1β-induced ECM degradation, proliferation arrest, and apoptosis enhancement in human chondrocytes by regulating the miR-140-3p/EZH2 axis [ 139 ]. The circRNA derived from vacuolar ATPase assembly factor ( VMA21 ) suppresses LPS-induced chondrocyte apoptosis in OA by decreasing the production of mature miR-103 [ 140 ].…”
Section: Ncrnas Involved In Cartilage Homeostasis and Oamentioning
confidence: 99%
“…Hence, hsa_circ_0027914 might down-regulate miR-140-3p through a competitive endogenous mechanism and lead to upregulation of DEGs in OA. A recent study has also reported that another circRNA (i.e., hsa_circ_0104595) can sponge miR-140-3p, then target EZH2 (enhancer of zeste homolog 2) to induce apoptosis of chondrocytes in OA ( 44 ). Furthermore, when the effect of si-circ-0027914 in reducing apoptosis is taken into consideration, there are reasons to believe that hsa_circ_0027914 plays a vital role in regulating multiple miRNAs and the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…All individuals participating were informed of the study and signed informed consent. e protocol of this work was approved by the Ethics Committee of Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology [16].…”
Section: Methodsmentioning
confidence: 99%